Individualized atrophy scores predict dementia onset in familial frontotemporal lobar degeneration. Issue 1 (6th January 2020) - Staffaroni, Adam M.; Cobigo, Yann; Goh, Sheng‐Yang M.; Kornak, John; Bajorek, Lynn; Chiang, Kevin; Appleby, Brian; Bove, Jessica; Bordelon, Yvette; Brannelly, Patrick; Brushaber, Danielle; Caso, Christina; et al.
Abstract: Introduction: Some models of therapy for neurodegenerative diseases envision starting treatment before symptoms develop. Demonstrating that such treatments are effective requires accurate knowledge of when symptoms would have started without treatment. Familial frontotemporal lobar degeneration offers a unique opportunity to develop predictors of symptom onset. Methods: We created dementia risk scores in 268 familial frontotemporal lobar degeneration family members by entering covariate‐adjusted standardized estimates of brain atrophy into a logistic regression to classify asymptomatic versus demented participants. The score's predictive value was tested in a separate group who were followed up longitudinally (stable vs. converted to dementia) using Cox proportional regressions with dementia risk score as the predictor. Results: Cross‐validated logistic regression achieved good separation of asymptomatic versus demented (accuracy = 90%, SE = 0.06). Atrophy scores predicted conversion from asymptomatic or mildly/questionably symptomatic to dementia (HR = 1.51, 95% CI: [1.16, 1.98]). Discussion: Individualized quantification of baseline brain atrophy is a promising predictor of progression in asymptomatic familial frontotemporal lobar degeneration mutation carriers.